Cdc2 activation is not required for thymocyte apoptosis. - Norbury, C; MacFarlane, M; Fearnhead, H; Cohen, G (1994)
Apoptosis is a mode of cell death characterized by chromatin condensation and disassembly of the nuclear lamina, processes that are also characteristic of mitosis. The apparent similarity between the two events, together with observations that apoptosis can occur following G2 arrest, has led to the suggestion that apoptosis could be a defective form of mitosis. Further support for this idea comes from the recent description of activation of the p34cdc2 protein kinase (Cdc2), the universal M-phase promoter, during death induced by a lymphocyte granule protease. We have monitored the protein kinase activity of Cdc2 during apoptosis of primary rat thymocytes, which die from a quiescent (G0) state. We demonstrate unequivocally that activation of Cdc2 is not involved in the induction of apoptosis in thymocytes, indicating that chromatin condensation and lamina disassembly occur in this system by processes different from those that operate in mitosis.